Fluorometric probing of the lipase level as acute pancreatitis biomarkers based on interfacially controlled aggregation-induced emission (AIE). Issue 9 (6th July 2017) - Shi, Jie; Deng, Qianchun; Wan, Chuyun; Zheng, Mingming; Huang, Fenghong; Tang, Bo
Abstract : We demonstrate a sensitive, easy and fast method for the fluorometric probing of the lipase level as acute pancreatitis biomarkers based on the novel interfacially controlled aggregation-induced emission (AIE) mechanism. Abstract : As a sudden inflammation of the pancreas, acute pancreatitis presents severe complications and a high mortality rate, despite treatment. Lipase in serum serves as an essential biomarker of acute pancreatitis and even pancreatic cancer. Therefore, developing robust, convenient and sensitive probing of lipase levels is greatly needed. In this work, we present glutamate functionalized tetraphenylethylene (TPE) as a "turn-on" fluorescent probe (S1 ) based on the aggregation-induced emission (AIE) mechanism for lipase levels with new recognition units. In heterogeneous media, the hydrophilic amino and carboxyl groups in the probe were specifically introduced to facilitate its full access to lipase at the oil–water interface and achieve an interfacially controlled AIE process. The linear response of fluorescence ranging from 0 to 80 U L −1, which included the concentration range of the lipase level in human serum, considering the dilution factor if necessary, the limit of detection as low as 0.13 U L −1, and the fast response time (7 min) were determined. The value of the apparent Michaelis–Menten constant ( K m ) was obtained as 4.23 μM, which indicated superior affinity between lipase and the probe molecule. The selectivity, photostability, dynamic monitoring of the enzymatic reaction, and preliminary commercial enzyme activity screening were summarized. As far as we know, this is the fastest, easiest and most sensitive method for lipase level probing in the reported literature. Finally, probing the lipase level for the first time in real human serum samples was also conducted successfully.